Effect of dietary crude protein and energy content on nitrogen utilisation, water intake and urinary output in growing pigs - Valaja, Jarmo; Siljander-Rasi, Hilkka (Agricultural and Food Science, 1998)
A digestibility and balance trial was carried out with four intact castrated male pigs (live weight 33-82 kg) to study the effects of dietary crude protein and energy content on nutrient digestibility, nitrogen metabolism, water intake and urinary output. In a 4 x 4 Latin square design, four barley-oats-soya bean meal based diets were arranged 2x2 factorially. The corresponding factors were dietary crude protein (CP) content: high (180 g/kg CP) or low protein diet (140 g/kg CP) supplemented with free lysine, methionine and threonine; and dietary net energy content; high (1.05 feed units (FU)/kg) (feed unit=9.3 MJ net energy) or low net energy content (0.95 FU/kg). Lowering dietary CP content (mean values of 189 to 152 g/kg dry matter, respectively) by supplementation of free amino acids decreased urinary nitrogen (N) excretion by 6.9 g/day (32%) (P<0.01) with no effect on faecal N excretion. Dietary protein reduction also increased the proportion of N retained per unit intake (P<0.10) and absorption (P<0.05). Daily N retention of pigs tended to decline with reduced dietary CP content (P<0.10). Dietary energy intake had no effect on N metabolism. Water intake and urinary output of pigs was unaffected by variations in protein and energy content which may be due to limitations in change-over experimental designs. The present experiment clearly demonstrated benefical effects of lowering dietary protein supply by free amino acid supplementation on N excretion.